Optical biosensors for environmental monitoring: Recent advances and future perspectives in bacterial detection - Sharma, Kajal; Sharma, Meenakshi (Environmental research, 2023)
The environmental contamination due to bacterial proliferation vs their identification is the major deciding factor in the spread of diseases leading to pandemics. The advent of drug-resistant pathogenic contaminants in our environment has further added to the load of complications associated with their diagnosis and treatment. Obstructing the spread of such infections, prioritizes the expansion of sensor-based diagnostics, effectuating, a sturdy detection of disease-causing microbes, contaminating our surroundings in shortest possible time, with minimal expenditure. Among many sensors known, optical biosensors promote the recognition of pathogens befouling the environment through a comparatively intuitive, brisk, portable, multitudinous, and thrifty approach. This article reviews the recent progresses in optical biosensor-based systems for effective environmental monitoring. The technical and methodological perspectives of fundamental optical-sensing platforms are reviewed, combined with the pros and cons of every procedure. Eventually, the obstacles lying in the path of development of an effective optical biosensor device for bio-monitoring and its future perspectives are highlighted in the present work. [Display omitted] •The potential of optical biosensors was explored with subject to environmentalmonitoring.•Utilization of bacteria as environmental contaminants as well as pollution indicators has been emphasized upon.•Pros and cons associated with various optical techniques have been described.•Future outlook for the manufacturing of sensor-based devices for pollution control has been elucidated.